Suriname. Significant achievements 2013 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Suriname during 2013 are identified, with respect to the needs and interests of the country, strengthening issues such as plant health, markets, zootechnics, livestock, agritourism, food safety, good agricultural practices, good manufacturing, sustainable agriculture, use of nurseries, crop control and control of pests such as fruit flies. Finally, support was given to improving veterinary medicine, the value chains of moringa and small ruminants.